BIBLIOMETRIC ANALYSIS OF ISLAM AND COVID-19 RESEARCH: WHAT WE HAVE LEARNT? - Muslim Ismail-Ahmad,; Shafiza Safie,; Zulkifli Mohamed,; Rohazlyn Rosly, (Journal of Islamic, Social, Economics and Development, 2022)
Islam and Covid-19 research are the main topics of this study. This bibliometric study analysed research papers published in Scopus related to the topic of Islam and Covid-19. Scopus database was chosen and publication data was extracted in February 2021. Research in this topic is relatively new judging from the retrieved research paper collected in the data collection process. From the retrieved result of 56 paper, VOSviewer software was used to visualize the co-occurrence of key words in the data collection. Significance issues such as Hajj, Umrah, Ramadan fasting and how the Turkish government handles the issue of religious community such as mass congregation in Friday Jumaah and so on. This paper concludes that current researches are concerned on issues of travelling to Kingdom of Saudi Arabia. Ramadan fasting is also an issue with the emergence issue of vaccines.